Resource allocation for FDMA-based regenerative multihop links. - Dohler, M. (IEEE Transactions on wireless communications)
An approximate but explicit fractional bandwidth and power allocation algorithm for orthogonal regenerative frequency-division multiple-access-based multihop communication systems over ergodic flat-fading channels is presented. The exposed algorithm is assessed for a two-hop scenario, where it is shown to operate within 10% of the optimum resource allocation. The achieved end-to-end capacity is up to 45% higher if compared to a trivial allocation strategy with equal resources.